Penerapan Kewenangan Diversi Terhadap Anak Yang Berhadapan Dengan Hukum - Cucun Cundaya Fitria Sari; Gios Adhyaksa; Suwari Akhmaddhian; Muhammad Raihan Pratama (JURNAL HUKUM PELITA, 2025)
Abuse of position through extortion constitutes a form of power misuse that significantly The purpose of this study is to determine and analyze the regulation and application of the prosecutor's authority in implementing diversion for children in conflict with the law in Cirebon Regency and Kuningan Regency. The analytical method used in this study is empirical juridical, namely a type of legal research that examines applicable legal provisions and what happens in reality in society. The con-clusion of this study is that the prosecutor's authority has been regulated in Article 7 and Article 42 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System along with other relevant regulations, and regulates limitations on the types of cases that can be diverted, which actually becomes an obstacle, because it shows that not all children who are perpetrators of crimes can be diverted. In addition, in its implementation, diversion is still faced with technical and cultural obstacles. Thus, the suggestions that can be recommended in this study are that policy makers need to revise or improve regu-lations governing diversion so that limitations that hinder the implementation of diversion efforts can be reviewed, and there is a need for increased socialization and education to the community and victims regarding the importance of diversion in protecting children's rights, as well as strengthening synergy between law enforcement agencies and social service providers to support the effectiveness of diversion im-plementation in the field